The impact of tourist’s intention to use Web 3.0: a conceptual integrated model based on TAM & DMISM - Mohammed Albaom, Mohammed Abdo; Sidi, Fatimah; A. Jabar, Marzanah; Abdullah, Rusli; Ishak, Iskandar; Yunikawati, Nur Anita; Priambodo, Magistyo Purboyo; Husen, Jati Hiliamsyah; Issac, Ossama; Al-Harasi, Abdo Hasan (Little Lion Scientific, 2021)
The rapid revolution of information technology has enhanced the global tourism industry that positively changed the structure of economy in large scale. Today, tourists face difficulties to find information to meet their needs or exceed their expectations due to the huge amount of information in the current Web and tourism portals. This has made the tourists or travelers decision to visit a particular destination very difficult. The main purpose of this research is to propose a conceptual integrated model to determine the factors influencing tourist’s intentions to use Web3.0. Therefore, despite the enormous transformative innovation that the Web3.0 will provide, there is still a significant gap between the current applied systems and the new technology at this moment. Besides that, the literature has shown that there are only few publications that used integrated theoretical model of Technology Acceptance Model (TAM) and Delone and Mclean Information System Model (DMISM) to investigate tourist’s intention to use new technology particularly Web 3.0. In addition, this research not only defines Web3.0, but also determines the possible challenges, risks, and opportunities that are emerged from Web3.0 technology specifically in the tourism domain. Moreover, while Web3.0 is prominent across businesses, there is surprisingly very limited academic work devoted to study its effect on consumer’s intentions to use and the tourism industry is not an exception. Consequently, this study will provide more insights, advance our understanding and contribute to this growing area of research as well as the proposed integrated conceptual model can serve as fundamental framework to be used in different domains.